2009
DOI: 10.1371/journal.pgen.1000397
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Analysis of Histidine Repeats Reveals Their Role in the Localization of Human Proteins to the Nuclear Speckles Compartment

Abstract: Single amino acid repeats are prevalent in eukaryote organisms, although the role of many such sequences is still poorly understood. We have performed a comprehensive analysis of the proteins containing homopolymeric histidine tracts in the human genome and identified 86 human proteins that contain stretches of five or more histidines. Most of them are endowed with DNA- and RNA-related functions, and, in addition, there is an overrepresentation of proteins expressed in the brain and/or nervous system developme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
137
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 135 publications
(151 citation statements)
references
References 82 publications
6
137
0
Order By: Relevance
“…FoxG1 is a nuclear protein bearing a poly-histidine (His) repeat (11 His, amino acids 47-57) in its N-terminal part. As observed in our work, it has been shown that loss of DNA binding in other poly-Histidine(His)-containing nuclear proteins (such as the transcription factor MEOX2) [Salichs et al 2009] with a point mutation is associated with their localization in intranuclear speckles. Recently, Ricciardi and colleagues showed that the product of the CDKL5 gene, which is involved in the early onset seizure variant of Rett syndrome, also localizes in nuclear speckles that are involved in the pre-mRNA processing in cells [Ricciardi et al 2009].…”
Section: Discussionsupporting
confidence: 63%
“…FoxG1 is a nuclear protein bearing a poly-histidine (His) repeat (11 His, amino acids 47-57) in its N-terminal part. As observed in our work, it has been shown that loss of DNA binding in other poly-Histidine(His)-containing nuclear proteins (such as the transcription factor MEOX2) [Salichs et al 2009] with a point mutation is associated with their localization in intranuclear speckles. Recently, Ricciardi and colleagues showed that the product of the CDKL5 gene, which is involved in the early onset seizure variant of Rett syndrome, also localizes in nuclear speckles that are involved in the pre-mRNA processing in cells [Ricciardi et al 2009].…”
Section: Discussionsupporting
confidence: 63%
“…Materials-Cloning of the following EGFP fusion protein expression vectors is described elsewhere: Sp100 (21), coilin (22), Sam68 (23), Cbx4 (24,25), Bmi-1 (26), Sc35 (27). nalaskowski@uke.uni-hamburg.de.…”
Section: Methodsmentioning
confidence: 99%
“…Overexpressed IP3KB/EGFP fusion proteins did not show this localization (data not shown). Using co-localization studies in H1299 cells, we showed that these nuclear structures are not identical with PML bodies (21), Cajal bodies (22), Sam68 nuclear bodies (23), polycomb bodies (24,25,26), or nuclear speckles (27) (data not shown). However, a co-localization with Ins(1,4,5)P 3 receptor type I and III (Fig.…”
Section: Ip3kb Is Enriched At Nuclear Invaginations Traversing Deeplymentioning
confidence: 97%
“…In addition, the threonine-proline repeats of SF3b1 (Eilbracht et al 2001) and the forkhead-associated domain in NIPP1 (Jagiello et al 2000) have also been implicated in speckle-targeting. Most recently, Salichs et al (Salichs et al 2009) performed a genomewide analysis of homopolymeric histidine tracts and identified 86 human proteins that contain stretches of five or more histidines. Of the 22 Structured illumination microscopy, using the OMX system (Applied Precision, Issaqua, Washington), of a HeLa cell expressing SC35-EYFP.…”
mentioning
confidence: 99%